Naltrexone sustained-release/bupropion sustained-release for the management of obesity: review of the data to date - Caixàs A; Albert L; Capel I; Rigla M (Dove Medical Press, 2014)
Assumpta Caixàs, Lara Albert, Ismael Capel, Mercedes Rigla Endocrinology and Nutrition Department, Parc Tauli Sabadell University Hospital, Autonomous University of Barcelona, Barcelona, Spain Abstract: Obesity is an emerging disease worldwide. Changes in living habits, especially with increased consumption of high-calorie foods and decreased levels of physical activity, lead to an energy imbalance that brings weight gain. Overweight and obesity are major risk factors for several chronic diseases (including cardiovascular diseases, diabetes, and cancer), reduce quality of life, and are associated with higher mortality. For all these reasons, it is of the utmost importance that the trend be reversed and obese people enabled to lose weight. It is known that eating a healthy diet and exercising regularly can help prevent obesity, but data show that in many cases these steps are not enough. This is the reason why, over the last few decades, several antiobesity drugs have been developed. However, the disappointing results demonstrated for the vast majority of them have not discouraged the pharmaceutical industry from continuing to look for an effective drug or combination of drugs. The systematic review presented here focuses on naltrexone sustained-release/bupropion sustained-release combination (Contrave®). We conclude from the current published reports that its effectiveness in the treatment of obesity can be estimated as a placebo-subtracted weight loss of around 4.5%. This weight reduction is moderate but similar to other antiobesity drugs. The safety profile of this combination is acceptable, despite additional data regarding cardiovascular disease being needed. Keywords: Contrave, weight loss, overweight, cardiovascular disease, diabetes, cancer